STRATEGI PENGEMBANGAN DESA WISATA DAWUHAN, KECAMATAN WANAYASA, KABUPATEN BANJARNEGARA - Fauzia, Salsabila Azzahra; Marom, Aufarul; Nurcahyanto, Herbasuki (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
Dawuhan Tourism Village is a highland tourist destination located in Dawuhan Village, Wanayasa District, Banjarnegara Regency. Dawuhan Tourism Village has the potential for a natural tourism area in the form of beautiful mountains and the Panaraban River with its flagship tourist attraction being the Rengrang Market. However, during its development, the tourist village faced several problems such as the quality of human resources in Pokdarwis as managers which was still lacking, facilities and infrastructure that were not adequate and well maintained, and road accessibility which was still damaged. This research aims to analyze internal and external environmental conditions and formulate strategies for efforts to develop the Dawuhan Tourism Village. The research method used is descriptive qualitative with data collection techniques through observation, interviews, questionnaires, and literature study. This research uses the strategic planning theory proposed by John. M. Bryson with SWOT analysis techniques and litmus tests to formulate the right strategy. The results of the research from the SWOT analysis found that there were 11 strategic development issues and a litmus test had been carried out to obtain 6 issues with a strategic nature, 3 of which had the highest scores that could be applied in tourism development. To obtain the highest score, one of them is included in the Comparative Advantage group where the Dawuhan Tourism Village can maximize its strengths by taking advantage of the opportunities that exist in efforts to develop the Dawuhan Tourism Village. Suggestions from this research include utilizing Pokdarwis collaboration with various tourism stakeholders in planning to manage and build tourist attractions; establishing training and education; increasing investors to support budget availability for developing infrastructure; increasing cooperation with the community for maintenance of infrastructure; developing the concept of local wisdom-based tourist villages as tourist attractions, and increasing BUMDes participation in tourism activities.